Rape—Brassica napus L. - James M. Stephens (EDIS)
This document provides an overview of the rape plant (Brassica napus L.), a cool-season annual related to turnip and rutabaga. It describes the plant’s characteristics, cultivation practices suitable for Florida, and its uses. While not commercially significant in Florida, rape can be grown successfully and is valued for its edible leaves, livestock fodder, and seed oil. The document also outlines the plant’s nutritional composition and historical uses, including oil production for lamps and lubrication. Original publication date May 1994.